Hubungan antara penguasaan penggunaan ejaan dan minat baca dengan keterampilan menulis narasi siswa kelas iv sd - Noella Adil Abita; Slamet Slamet (Didaktika Dwija Indria, 2025)
The purpose of this study is to demonstrate how the narrative writing skills of fourth-grade students (Y) relate to their mastery of spelling (X1) and reading interest (X2). Using a correlational design, the study involved all fourth-grade students in public elementary schools in Manyaran sub district during the 2024/2025 academic year, with cluster random sampling. The data collection methods used are questionnaires and tests. Data were collected through questionnaires and tests, and analyzed using simple and multiple correlation techniques. The findings reveal a strong and significant correlation between spelling mastery and writing skills (r = 0.96, t = 24.7 > t-table 1.67), as well as between reading interest and writing skills (r = 0.98, t = 39.4 > t-table 1.67). Combined, both variables significantly correlate with narrative writing skills (r = 0.986, F = 927.18 > F-table 3.168, α = 0.05, df = 54).